Literature Review: Metode Webqual 4.0 dalam Pengukuran Kualitas Website - Wisnu Ranggaadhya Kusumawardhana (SABER : Jurnal Teknik Informatika, Sains dan Ilmu Komunikasi, 2025)
At this time, technological development is something that cannot be avoided. This is because technological development goes hand in hand with the development of science. One of the technological developments that is growing rapidly at this time is the information system. The method used in this study uses the WebQual method, measuring based on the quality of the distribution function (quality function deployment) or commonly called QFD, which is a structured and disciplined process that provides a means to identify and bring customer aspirations through each stage of product and or service development and its implementation. WebQual 4.0 is a measurement to measure website quality based on research instruments that can be categorized into four variables, namely usability, information quality, interaction quality, and overall impression. The WebQual 4.0 method is widely used to show the quality of the website or application used. With many articles discussing the analysis of user experience using the webqual 4.0 method, it has proven effective in assessing usability, information quality, and service interaction quality of an application or website.